2011
DOI: 10.1177/1352458511422926
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heat stress on cognition in persons with multiple sclerosis

Abstract: A significant increase in core body temperature during heat stress is associated with a mild and reversible worsening of the PASAT 3" performance, while visual vigilance performance seems to remain almost unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
2
22
1
Order By: Relevance
“…The results on the effects of heat on cognition will be presented in a separate report [21]. Assessments were conducted at baseline and immediately, at 1 hour, as well as at 24 hours following the heat exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The results on the effects of heat on cognition will be presented in a separate report [21]. Assessments were conducted at baseline and immediately, at 1 hour, as well as at 24 hours following the heat exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous publications we reported that the core body temperature of MS patients rises more during heat exposure than that of the HCs and that heat temporarily impairs the cognitive and physical performance of MS patients with heat sensitivity (1,2). In the present study, the data from our previous studies were further analyzed to determine whether the heat-induced decline is observed with the MSFC composite score.…”
Section: Discussionmentioning
confidence: 88%
“…The study was conducted in Masku neurological rehabilitation center (Finland), and the study group used in the current analysis was the same as our previous studies (1,2). In total, 22 individuals with MS and 19 healthy controls were included in the analysis.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, cognitive fatigue is quite visible during cognitive tasks. 10 The necessity of early intervention is emphasized and can be achieved by an individually tailored program, through a multimodal neuropsychological approach if necessary because of widespread cognitive impairment. …”
mentioning
confidence: 99%